Introduction. Politiques urbaines et inégalités en Méditerranée - Hend Ben Othman Bacha; Olivier Legros (Les Cahiers d’EMAM)
This document includes several contributions to the workshop “Urban policies and the production of socio-spatial inequalities in the Mediterranean in neoliberal times” which took place in Tunis on the 28 and 29 March 2014 as part of the ANR “Marges et villes : entre exclusion et intégration. Cas méditerranéens”, program led by Nora Semmoud (UMR CITERES EMAM, University of Tours/CNRS). It presents the themes that served to frame the Tunis workshop and highlights the main contributions of case studies gathered in this document. Thus, these points are raised: the impact of major development projects and, more broadly, urban policy on the social divisions of the urban space; the local mobilizations in neighborhoods threatened by eviction and the developments since popular uprisings in the Arab world in the early 2010s, particularly in regard to the attitude of the authorities to the developments of informal housing.